An offer from a gentleman - Quinn, Julia, 1970- (Quinn, Julia, 1970- Bridgerton series., 2015)
While searching for a mysterious beauty he met at a masquerade party, Benedict Bridgerton meets Sophie Beckett, a servant in need of his help, and as passion flares between them, he must choose between Sophie and the woman of his dreams.